The death penalty and sex murder in Canadian history - Strange, Carolyn, 1959- (Osgoode Society for Canadian Legal History series., 2020)
"From Confederation to the partial abolition of the death penalty a century later, defendants convicted of sexually motivated killings and sexually violent homicides in Canada were more likely than any other condemned criminals to be executed for their crimes. Despite the emergence of psychiatric expertise in criminal trials, moral disgust and anger proved more potent in courtrooms, the public mind, and the hearts of the bureaucrats and politicians responsible for determining the outcome of capital cases. Outsiders of all types--drifters, the unemployed, the unconventional--were the first to fall within the radar of police who were pressured to catch culprits. Although the vast majority of convicted sex killers were white, Canada's racist notions of "the Indian mind" meant that Indigenous defendants faced the presumption of guilt. Black defendants were also subjected to discriminatory treatment, including near lynchings. Even prior to Steven Truscott's controversial death sentence for a sex murder in 1959, abolitionists expressed concern that prejudices and poverty created the prospect of wrongful convictions. Unique in the ways it reveals the emotional drivers of capital punishment in delivering inequitable outcomes, The Death Penalty and Sex Murder in Canadian History provides a thorough overview of sex murder and the death penalty in Canada. It serves as an essential history and a richly documented cautionary tale for the present."--